Optimisation of manufacturing parameters for inkjet‐printed and photonically sintered metallic nanoparticle UHF RFID tags. Issue 21 (1st October 2014) - Ren, Y.; Virkki, J.; Sydänheimo, L.; Ukkonen, L.
Abstract : Inkjet printing and photonic sintering parameters for silver and copper nanoparticle inks on flexible polyimide and environmentally friendly cardboard substrates have been studied. The results were utilised to manufacture prototype passive ultra‐high frequency (UHF) radio‐frequency identification (RFID) tag antennas. The manufactured tags showed peak read ranges of 2.9–5.5 m.